Camptostemon philippinensis, a new record of endangered mangrove species in the Balikpapan Bay, East Kalimantan, Indonesia [version 3; peer review: 1 approved, 2 approved with reservations] - Burhanuddin Adman; Istiana Prihatini; Mukhlisi Mukhlisi; Tri Atmoko; Bina Swasta Sitepu; Abdul Razaq Chasani (F1000Research)
Background Camptostemon philippinensis, found in mangrove forests in Indonesia and the Philippines, is listed as endangered on the International Union for Conservation of Nature (IUCN) Red List. It is found primarily in isolated mangrove forests in Kalimantan (Indonesian Borneo) and Sulawesi in Indonesia. Despite significant studies on mangrove biodiversity in this region, the occurrence of C. philippinensis in Balikpapan Bay, East Kalimantan, is not extensively recorded. Methods The study was conducted by exploring the mangrove forests along Balikpapan Bay. The first survey of about 200 km was conducted to observe mangrove vegetation and found one C. philippinensis tree. The second survey focused on the area around the first discovered C. philippinensis tree to census and record its growth stage and distribution. Results The study recorded a population of 527 individuals of C. philippinensis in Pantai Lango Village, East Kalimantan, dominated by seedlings. The high number of seedlings indicates good natural regeneration potential, but the low number of trees indicates intense competition for space in a restricted habitat. This species inhabits a small and restricted area in Balikpapan Bay, in the middle area of Balikpapan Bay, and is associated with other mangrove flora, such as Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, Avicennia alba, Lumnitzera littorea, Osbornia octodonta, Ceriops tagal, and Xylocarpus granatum. Conclusions C. philippinensis is vulnerable to habitat damage from anthropogenic activities, which could lead to local extinction. Its natural habitat in Balikpapan Bay also has the potential to be under pressure due to the development of Indonesia’s new capital city (Ibu Kota Nusantara/IKN). It emphasizes the need to understand the ecological role of this protected flora in the natural habitat of protected fauna (the proboscis monkey). Documenting the population of C. philippinensis is crucial for conservation efforts, including propagation and understanding its ecological role.